Improved correction for gradient nonlinearity effects in diffusion‐weighted imaging. Issue 2 (21st November 2012) - Tan, Ek T.; Marinelli, Luca; Slavens, Zachary W.; King, Kevin F.; Hardy, Christopher J.
<x xml:space="preserve">Abstract</x> Purpose To provide an improved correction for gradient nonlinearity (GN) effects in diffusion‐weighted imaging (DWI). These effects produce spatially varying apparent diffusion coefficient (ADC), a result that will be significant in large field‐of‐view imaging, and may be confounded by distortion and concomitant fields related to the DWI acquisition. Materials and Methods The effect of more accurate gradient field maps on GN correction (GNC) of ADC was evaluated. A simulation compared GN effects in commonly imaged anatomy. A temperature‐controlled phantom was imaged at positions 0 cm and 11 cm from isocenter and in two whole‐body MRI systems at 1.5T with different patient bore diameters (55 cm and 60 cm). Varying correction methods were applied to determine the errors from spatial variance and interscanner reproducibility. Results As compared to conventional fifth‐order spherical harmonics, a seventh‐order GNC improved ADC accuracy by 1%. The combination of GNC with a dual‐spin‐echo pulse sequence and a retrospective concomitant field correction reduced ADC error due to spatial variance from 9.5% to 1.8% (55 cm bore) and from 4.2% to 1.8% (60 cm bore). The error in ADC attributed to interscanner reproducibility was reduced from 5.8% to 0.15% (at isocenter) and from 10% to 0.63% (11 cm from isocenter). Conclusion GNC in DWI improved spatial accuracy and interscanner reproducibility of ADC. J. Magn. Reson. Imaging 2013;38:448–453. © 2012 Wiley Periodicals, Inc.